Fatores críticos de sucesso para a formatação de um empreendimento imobiliário voltado para pessoas idosas em Curitiba/PR - Morais, Priscila Pedroso (2020)
To find out what are the critical success factors of a real estate development aimed at the elderly in Curitiba / PR, some objectives were determined, such as To identify which target audience will be reached with a development of this profile, identify what is the real need that the elderly home owners, and measure with performance indicators if the venture can be characterized as profitable for investors. For this, it was identified that because it is a project with a high cost, the audience that will be reached will be class A and B, aimed at seniors who want a quiet life, with all the accessibility, privacy and comfort that everyone wants. To characterize the needs, the Delphi methodology was used, where several specialists from different areas answered questionnaires with varied themes until reaching a consensus demanded by the researcher, discovering what are the real difficulties and challenges that have in a home for the elderly. The indicators that were used to measure were PAYBACK, internal rate of return and net present value. From the Delphi questionnaires, some results were obtained as: the need to have a whole adapted place só that many domestic accidents are avoided and the emotional need that an elderly person has to feel alone, often causing terminal illnesses. These and other problems can be avoided with an adapted structure and living with people who are going through the same kind of situation. Through an analysis of results, it was observed that for a 25-year project, profitability is positive, with an 8-year PAYBACK, positive NPV and 12% IRR, with a Selic rate of 200%, using a cost of capital of 11.8%. Some subjects were identified as possible future projects, such as: the possibility of redoing the same work with focusing on another city / state and a case study with older people also answering the questionnaires, building a broader and more assertive study on the needs than the others elderly have.